Determinants of Open Unemployment in Papua and New Autonomous Regions: A Panel Data Analysis - Trisnawati Trisnawati; Mesak Iek; Yundy Hafizrianda (Global Academy of Business Studies, 2026)
Purpose: This study examines the effects of economic growth, education level, inflation, and labor force participation on the Open Unemployment Rate (OUR) across Papua Province and its three New Autonomous Regions (NARs) Papua Selatan, Papua Tengah, and Papua Pegunungan during the 2017–2024 period. Research Methodology: This research employed a quantitative approach using panel data regression analysis based on secondary data obtained from BPS (Statistics Indonesia). Model selection was determined through Chow, Hausman, and Lagrange Multiplier tests, resulting in the use of Fixed Effect Model (FEM) and Random Effect Model (REM) specifications. Classical assumption tests included normality, multicollinearity, and heteroscedasticity diagnostics, with robust standard errors applied to heteroscedastic models. Data analysis was conducted using STATA. Results: Economic growth significantly reduced unemployment in Papua Selatan, Papua Pegunungan, and the pooled model, but was insignificant in Papua and Papua Tengah. Education significantly affected unemployment in all provinces with varying directions, indicating labor market mismatch. Inflation was insignificant, while labor force participation was significant only in Papua Tengah. Conclusions: Unemployment dynamics in Papua are structurally heterogeneous and require province-specific employment policies emphasizing labor-intensive sector development, vocational education alignment, and informal sector formalization. Limitations: This study is limited to macroeconomic indicators and secondary panel data at the regency/city level. Contributions: This study contributes to the literature on regional labor market disparities in post-autonomy Papua by providing empirical evidence on asymmetric unemployment determinants across newly established autonomous regions.